Pengaruh Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Karyawan Pada PT. Segar Prima Laksana Muara Bungo - Hamirul, Hamirul; Sunaryo, Joko; M, Ariyanto; Zulkifli, Zulkifli; Rusnaini, Sasmita; Tarjo, Tarjo (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2022)
The purpose of this study is to determine the influence of leadership and organizational culture on employee performance. The research method used is the quantitative method. This type of research is causal associative. The research instrument used a questionnaire. The population in this study were all employees at PT. Fresh Prima Like Muara Bungo. And this study uses a saturated sampling technique, where all members of the population are used as samples. The sample of this study was 50 people, and the entire population was sampled. The data analysis technique used is multiple linear regression, classical assumption test, hypothesis testing and coefficient of determination test. The data analysis techniques were all tested using SPSS version 25 software. The results of the t test, H1 is accepted, leadership has an influence on employee performance, with a value of Tcount 2.785 T table 2.011 with a significance level of 0.008 0.05. H2 is accepted, organizational culture has an influence on employee performance, with a value of Tcount 2.029 T table 2.011 with a significance level of 0.048 0.05. The results of the f test, H3 is accepted, leadership and organizational culture have an influence on employee performance, with a value of Fcount 10,477 Ftable 3,195 with a significance level of 0.000 0.05.